Experimental investigation of single blade loads by captive model tests in pure oblique flow. Part II: Propeller in-plane loads and preliminary comparison of single blade loads during transient phases. (15th August 2021) - Ortolani, Fabrizio; Tani, Giorgio; Viviani, Michele; Dubbioso, Giulio
Abstract: Off–design and realistic operative conditions of the propulsion system have been progressively considered a frontier topic for the development of novel and successful design procedures. The availability of high accurate data on propeller performance, both experimental or numerical, is pivotal for the development of reliable tools and the enhancement of traditional ones. In this context, this paper continues the investigation described in (Ortolani et al., 2020), that was dedicated to analyze the single blade loads obtained by oblique towing tests and assess their consistency with those measured during the steady turning phase, reproduced by free running model tests. In this paper, the same analysis is broadened to two aspects. At first, the in–plane forces and moments that are obtained by a conversion from the rotating frame of the measure to the fixed frame are discussed. These loads need quantification, because they are the primary cause of damages of the shafting structure, vibratory loads and also contribute to dynamic response of the ship. Then, the study is switched to the comparison of single blade loads during transient motions of the turning maneuvers, at weak and tight rudder angles, performed at the same reference speed as the captive model test. The analysis lays the basis for the enhancement of ship system (comprehensive) mathematical models, already used in ship design, to real–time analysis of vibratory loads and emitted noise. Highlights: Development and application of a novel setup for single blade loads measurements. Analysis in static drift condition and comparison with free running model tests. Phenomenological description of the generation of in-plane propeller loads. Asymmetric behavior for internal and external propellers of twin screw configuration. Preliminary analysis of blade loads during transient maneuvering.